A Time to Die: The « American Way of Life » in the Anthropocene - Joseph Nevins (Bulletin de l’Association de Géographes Français)
We live in a time of multiple, overlapping ecological crises, ones that threaten the very foundations upon which the contemporary world sits. This article asserts that the source of these crises is what we might call the “American way of life.” This way of life is tightly linked to high levels of consumption and consumerism, as well as to a particular form of political economy closely associated with the United States. Yet the way of life and the political-economic and military power that enables and upholds it go far beyond U.S. territorial boundaries. This is because they are embedded in a global constellation of socio-geographical relations; it is also because populations beyond the United States, members of what we might consider the planet’s ecologically privileged class, embrace and practice the high levels of consumption and consumerism that reflect and reproduce the “American” lifestyle. It is a lifestyle predicated on dys‑ecologism: the appropriation of an unsustainable and socially unjust share of the biosphere’s resources and, relatedly, the grossly unequal allocation of life and death circumstances across the planet. Thus, while the “American way of life” certainly benefits many, it contributes to the premature death of many more of the Earth’s denizens. It is, therefore, unsustainable in both an ecological sense and a socio-spatial justice one as well. For this reason and more, the article argues, the “American way of life” must be made to die.